High-performance carbon-carbon composite material and preparation method thereof

In the production of carbon-carbon composite materials, the immersion-carbonization process of controlling the deposition and adding carbon nanotubes to the impregnation agent is solved, and the problems of high cost and difficult to increase in traditional processes are achieved, achieving high efficiency and low cost Preparation of high-performance carbon-carbon composite materials.

CN119390467APending Publication Date: 2025-02-07ZHEJIANG CHAOTAN CARBON NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411307819.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The production cost of existing carbon-carbon composite materials is high, the traditional CVD process consumes power and has poor internal filling effect on large components. The impregnation-carbonization process has many cycles and low efficiency, making it difficult to reach more than 1.7g/cm3.

Method used

The carbon fiber braid was controlled by the CVD method, and then the impregnation-carbonization density-enhancing cycle was performed using an impregnation agent containing carbon nanotubes, and the carbon-carbon composite material was further filled by the CVD method.

Benefits of technology

By optimizing the CVD deposition and impregnation-carbonization process, the production cost is significantly reduced, the process time is shortened, the density and performance of carbon-carbon composite materials are improved, and the final density reaches 1.72-1.78g/cm3 is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390467A_ABST
    Figure CN119390467A_ABST
Patent Text Reader

Abstract

The invention relates to a high-performance carbon-carbon composite material and a preparation method thereof, and the preparation method comprises the following steps: (1) carrying out controlled deposition shaping on a carbon fiber woven body by adopting a CVD (Chemical Vapor Deposition) method to obtain a preformed body; (2) carrying out impregnation-carbonization densification cycle treatment on the preformed body by adopting an impregnant containing a carbon nano tube to obtain a compact carbon-carbon composite material; and (3) depositing the carbon-carbon composite material by adopting the CVD method again to obtain the high-performance carbon-carbon composite material. According to the invention, the CVD and impregnation-carbonization combined process is adopted, so that the manufacturing time can be greatly shortened, and the defect of long time of a pure CVD process is overcome; the density of the initial CVD preform is optimized, so that the proportion of an impregnant entering a matrix in the impregnation process is increased; the carbon residue rate of the impregnant is increased by further adding the carbon nanotubes into the impregnant, the defect of low carbon residue rate of the currently used impregnant is overcome, the cycle index of the impregnation-carbonization process is reduced, the time is saved, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-carbon composite materials, and in particular relates to a high-performance carbon-carbon composite material and a preparation method thereof. Background Art

[0002] Carbon-carbon composites are a type of high-performance composite material that has developed rapidly in recent years and has been widely used in the manufacture of structural and functional components. However, a major disadvantage of carbon-carbon composites is their high cost, with production costs ranging from thousands to tens of thousands of yuan per kilogram, which seriously restricts their application. Therefore, reducing production costs is currently the focus.

[0003] The traditional carbon-carbon composite material manufacturing process uses chemical vapor deposition (CVD) to deposit carbon fiber braids, and the deposition time is 800-1100 hours. The high-temperature deposition power consumption, equipment maintenance, and labor costs of the CVD process are all factors that restrict cost reduction; and for large components, since the early deposition is easy to block the reaction gas diffusion channel, the CVD filling effect on the inside is poor, and the final density is difficult to reach 1.6g / cm 3 There are also methods that use impregnating agents with short process time and relatively low cost to treat carbon fiber braids through an impregnation-carbonization process to increase density. This method requires multiple impregnation-carbonization cycles to achieve the designed performance and density values. Although the time and cost of a single impregnation-carbonization densification process are relatively low, the proportion of the impregnating agent that turns into carbon during carbonization is relatively low (50-60wt%), resulting in a large number of impregnation-carbonization densification process cycles, especially in the later stages of carbon-carbon composite material preparation, when the composite material density is relatively high (greater than 1.65g / cm 3 ) is difficult for the impregnating agent to enter the composite matrix, and the efficiency is extremely low, which makes it difficult to reduce the cost to the expected target. Some studies have combined the above two processes, that is, CVD deposition first, and then impregnation-carbonization to further increase the density. Compared with the simple CVD process, the entire production time is shortened and the production cost is reduced to a certain extent, but the final density is difficult to be higher than 1.7g / cm 3 ; Moreover, the density of the early CVD deposition is relatively high, which limits the entry of the impregnant, and the filling effect needs to be improved. Summary of the invention

[0004] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a high-performance carbon-carbon composite material and a preparation method thereof that meets one or more of the above-mentioned needs.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] A method for preparing a high-performance carbon-carbon composite material comprises the following steps:

[0007] (1) using a CVD method to control the deposition and shaping of a carbon fiber braid to obtain a preform;

[0008] (2) using an impregnating agent containing carbon nanotubes to perform an impregnation-carbonization densification cycle on the preform to obtain a dense carbon-carbon composite material;

[0009] (3) The carbon-carbon composite material is deposited again using the CVD method to obtain a high-performance carbon-carbon composite material.

[0010] As a preferred embodiment, in step (1), the density of the carbon fiber braid is 0.4-0.7 g / cm 3 The density of the preform is 0.12-0.2g / cm higher than that of the carbon fiber braid. 3 .

[0011] As a preferred embodiment, in step (1), the CVD method uses methane gas, which is cracked at a high temperature of 900-1300° C. and deposited for 40-60 hours.

[0012] As a preferred embodiment, in step (2), the impregnating agent for the carbon nanotubes is an impregnating agent obtained by mixing the carbon nanotubes with asphalt or resin by mechanical stirring.

[0013] As a preferred embodiment, the softening point of the asphalt in the impregnating agent is 90-120°C, the residual carbon rate is 50-61%, and the QI content is less than 2%; or, the resin in the impregnating agent is a thermosetting phenolic resin, and the concentration of the resin solution is 55-70%.

[0014] As a preferred embodiment, in step (2), the impregnation-carbonization process comprises: impregnating the preform with an impregnating agent under vacuum, and then carbonizing at 1000-1200° C. for 1-2 hours;

[0015] The number of impregnation-carbonization cycles is 3-6 times.

[0016] As a preferred embodiment, the density of the dense carbon-carbon composite material is 1.58-1.62 g / cm 3 .

[0017] As a preferred embodiment, if a mixture of carbon nanotubes and asphalt is used as an impregnating agent, the impregnation-carbonization process includes the following steps: placing the preform in a sealed container, heating it to a first target temperature, evacuating and maintaining the vacuum state; heating the impregnating agent to a first target temperature, the first target temperature is 80-100°C higher than the softening point of the asphalt, and the viscosity of the impregnating agent should be ensured to be less than 10 centipoise at this temperature, and after the impregnating agent is completely melted, it is pumped into the sealed container, pressurized and maintained for several hours, and then cooled to room temperature, and the product is taken out for carbonization;

[0018] If a mixture of carbon nanotubes and resin is used as the impregnating agent, the impregnation-carbonization process includes the following steps: heating the sealed container to a second target temperature, evacuating and maintaining the vacuum state; heating the impregnating agent to the second target temperature, and after the temperature stabilizes, pumping the impregnating agent into the sealed container, pressurizing and maintaining it for several hours, and then cooling it to room temperature, taking out the product for drying, curing, and carbonization; wherein the second target temperature is 100-110°C, at which temperature the viscosity of the impregnating agent is ensured to be less than 10 centipoise.

[0019] As a preferred solution, in step (3), the CVD method uses methane gas, which is cracked at a high temperature of 900-1300° C. and deposited for 50-70 hours.

[0020] The present invention also provides a high-performance carbon-carbon composite material prepared by the preparation method described in any of the above schemes, wherein the density of the high-performance carbon-carbon composite material is 1.72-1.78 g / cm 3 .

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention controls the CVD deposition degree during the shaping stage of the carbon fiber braid, so that the density of the CVD-filled braid is not too high. On the one hand, it prevents excessive CVD carbon deposition from blocking some of the braid gaps in the early stage of production, so that the filling amount of the impregnant in the impregnation-carbonization process is effectively increased; on the other hand, the proportion of impregnation-carbonization in the production process is increased, which can greatly reduce the process time and reduce costs;

[0023] (2) Since carbon nanotubes are pure carbon materials, they will all remain in the preform after carbonization. Therefore, the addition of carbon nanotubes to the impregnating agent in the present invention improves the densification efficiency after carbonization and can reduce the number of impregnation-carbonization cycles. At present, carbon nanotubes have been mass-produced at a cost of less than 500 yuan / kg. Compared with carbon-carbon composite materials costing thousands of yuan / kg, adding carbon nanotubes is economically advantageous. When the density of the carbon-carbon composite material exceeds 1.65g / cm 3When the carbon-carbon composite material has small voids, the impregnant is difficult to enter the composite material, and the impregnation-carbonization effect is not good. However, the methane molecules of CVD are small and can enter the interior of the composite material. At this time, further filling the carbon-carbon composite material with CVD can further increase the density and obtain a composite material with good performance.

[0024] (3) The present invention adopts a combined process of CVD and impregnation-carbonization to significantly shorten the production time, thus overcoming the shortcoming of the long time of the simple CVD process; optimizes the density of the initial CVD preform, thereby increasing the proportion of the impregnant entering the matrix during the impregnation process; further adopts a method of adding carbon nanotubes to the impregnant to increase the residual carbon rate of the impregnant, thereby overcoming the shortcoming of the low residual carbon rate of the currently used impregnant, reducing the number of impregnation-carbonization process cycles, saving time, and reducing costs; and when the density of the carbon-carbon composite material reaches 1.65 g / cm 3 When the density of the composite material is above 1.7 g / cm, CVD is used to fill the tiny gaps, so that the final density of the composite material can reach 1.7 g / cm 3 As mentioned above, the performance of carbon-carbon composite materials is effectively improved and has superior performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flow chart of the preparation process of a high-performance carbon-carbon composite material. DETAILED DESCRIPTION

[0026] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.

[0027] Comparative Example 1:

[0028] This comparative example adopts simple CVD to prepare carbon-carbon composite material, and the specific process is as follows:

[0029] The density is 0.46g / cm 3 The carbon fiber braid was deposited at 1150℃ for 1000 hours with methane as the carbon source gas, and the obtained carbon-carbon composite material had a density of 1.59g / cm 3 , the flexural strength is 135.7MPa.

[0030] Comparative Example 2:

[0031] The impregnating agent of this comparative example does not contain carbon nanotubes.

[0032] The preparation process of the carbon-carbon composite material of this comparative example is as follows:

[0033] The density is 0.46g / cm 3 The carbon fiber braid was deposited at 1100℃ for 52 hours with methane as the carbon source gas, and the density was 0.59g / cm 3 A preform;

[0034] Asphalt with a softening point of 102°C, a residual carbon rate of 56%, and a QI content of 1.4% was used as the impregnating agent;

[0035] The impregnation-carbonization process includes: placing the preform in a sealed container, heating it to 182°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 182°C, pumping it into the above-mentioned sealed container after the impregnating agent is completely melted, pressurizing it at 1MPa for 3 hours, then cooling it to room temperature, and carbonizing it at 1100°C for 2 hours after taking it out;

[0036] The above impregnation-carbonization cycle was repeated 4 times, and the density of the obtained dense carbon-carbon composite material was 1.43 g / cm 3 ;

[0037] Finally, methane was used for deposition at 1100 °C for 55 hours to obtain a carbon-carbon composite material with a density of 1.54 g / cm 3 , the flexural strength is 123.1MPa.

[0038] Embodiment 3:

[0039] like Figure 1 As shown, the preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0040] The density is 0.46g / cm 3 The carbon fiber braid was deposited at 1100℃ for 52 hours with methane as the carbon source gas, and the density was 0.59g / cm 3 A preform;

[0041] To asphalt with a softening point of 102°C, a residual carbon rate of 56%, and a QI content of 1.4%, 7% of carbon nanotubes with a diameter of 20-30nm and a length of 5-10 microns were added as an impregnating agent;

[0042] The impregnation-carbonization process includes: placing the preform in a sealed container, heating it to 182°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 182°C, pumping it into the above-mentioned sealed container after the impregnating agent is completely melted, pressurizing it at 1MPa for 3 hours, then cooling it to room temperature, and carbonizing it at 1100°C for 2 hours after taking it out;

[0043] The above impregnation-carbonization cycle was repeated 4 times, and the density of the carbon-carbon composite material was 1.59 g / cm 3 ;

[0044] Finally, methane deposition was performed at 1100 °C for 55 h to obtain a dense carbon-carbon composite with a density of 1.72 g / cm 3 , the flexural strength is 167.5MPa.

[0045] Compared with comparative example 2, the density of the carbon-carbon composite material prepared by using the carbon nanotube modified asphalt impregnating agent after the same process was increased by 13.0%, and the bending strength was increased by 36.1%. Compared with comparative example 1, the process time was greatly reduced by more than 70%, as shown in Table 1.

[0046] Embodiment 4:

[0047] The preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0048] The density is 0.62g / cm 3 The carbon fiber braid was deposited at 1200℃ for 55 hours with methane as the carbon source gas to obtain a density of 0.76g / cm 3 A preform;

[0049] To asphalt with a softening point of 108°C, a residual carbon rate of 58.5%, and a QI content of 1.6%, 5% of carbon nanotubes with a diameter of 20-30nm and a length of 5-10 microns were added as an impregnating agent;

[0050] The impregnation-carbonization process includes: placing the preform in a sealed container, heating it to 188°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 188°C, pumping it into the above-mentioned sealed container after the impregnating agent is completely melted, pressurizing it at 1MPa for 3 hours, then cooling it to room temperature, taking it out and carbonizing it at 1000°C for 2 hours;

[0051] The above impregnation-carbonization cycle was repeated 4 times to obtain a dense carbon-carbon composite material with a density of 1.58 g / cm 3 ;

[0052] Finally, methane was used for deposition at 1000 °C for 65 hours to obtain a carbon-carbon composite material with a density of 1.73 g / cm 3 , the flexural strength is 172.1MPa.

[0053] Embodiment 5:

[0054] The preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0055] The density is 0.40g / cm 3 The carbon fiber braid was deposited at 1300℃ for 40 hours with methane as the carbon source gas to obtain a density of 0.60g / cm 3 A preform;

[0056] To asphalt with a softening point of 120°C, a residual carbon rate of 61%, and a QI content of 1.9%, 6% of carbon nanotubes with a diameter of 20-30nm and a length of 5-10 microns were added as an impregnating agent;

[0057] The impregnation-carbonization process includes: placing the preform in a sealed container, heating it to 200°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 200°C, pumping it into the above-mentioned sealed container after the impregnating agent is completely melted, pressurizing it at 1MPa for 3 hours, then cooling it to room temperature, taking it out and carbonizing it at 1000°C for 2 hours;

[0058] The above impregnation-carbonization cycle was repeated 6 times to obtain a dense carbon-carbon composite material with a density of 1.62 g / cm 3 ;

[0059] Finally, methane was used for deposition at 1200 °C for 60 h to obtain a carbon-carbon composite with a density of 1.78 g / cm 3 , the flexural strength is 183.5MPa.

[0060] Embodiment 6:

[0061] The preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0062] The density is 0.40g / cm 3 The carbon fiber braid was deposited at 1300℃ for 40 hours with methane as the carbon source gas to obtain a density of 0.60g / cm 3 A preform;

[0063] A phenolic resin solution with a concentration of 70% was added with 8% carbon nanotubes with a diameter of 20-30nm and a length of 5-10 microns as an impregnating agent;

[0064] The impregnation-carbonization process includes: heating a sealed container to 105°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 105°C, pumping the impregnating agent into the sealed container after the temperature stabilizes, pressurizing it at 1MPa for 3 hours, and then cooling it to room temperature. After taking it out, the product is dried, cured, and carbonized, and the carbonization is carried out at 1100°C for 2 hours;

[0065] The above impregnation-carbonization cycle was repeated 6 times to obtain a dense carbon-carbon composite material with a density of 1.62 g / cm 3 ;

[0066] Finally, methane was used for deposition at 900 °C for 70 h to obtain a carbon-carbon composite with a density of 1.72 g / cm 3 , the flexural strength is 160.5MPa.

[0067] Embodiment 7:

[0068] The preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0069] The density is 0.70g / cm 3 The carbon fiber braid was deposited at 900℃ for 60 hours with methane as the carbon source gas, and the density was 0.82g / cm 3 A preform;

[0070] A 55% phenolic resin solution was added with 5% carbon nanotubes with a diameter of 20-30 nm and a length of 5-10 microns as an impregnating agent;

[0071] The impregnation-carbonization process includes: heating a sealed container to 105°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 105°C, pumping the impregnating agent into the sealed container after the temperature stabilizes, pressurizing it at 1MPa for 3 hours, and then cooling it to room temperature. After taking it out, drying, curing, and carbonizing the product, and carbonizing it at 1200°C for 1 hour;

[0072] The above impregnation-carbonization cycle was repeated three times to obtain a dense carbon-carbon composite material with a density of 1.58 g / cm 3 ;

[0073] Finally, methane deposition was performed at 1200 °C for 55 hours to obtain a carbon-carbon composite with a density of 1.73 g / cm 3 , the flexural strength is 162.1MPa.

[0074] Embodiment 8:

[0075] The preparation process of the high performance carbon-carbon composite material of this embodiment is as follows:

[0076] The density is 0.70g / cm 3 The carbon fiber braid was deposited at 900℃ for 60 hours with methane as the carbon source gas, and the density was 0.82g / cm 3 A preform;

[0077] To asphalt with a softening point of 90°C, a residual carbon rate of 55%, and a QI of 1.0%, 3% of carbon nanotubes with a diameter of 20-30nm and a length of 5-10 microns were added as an impregnating agent;

[0078] The impregnation-carbonization process includes: placing the preform in a sealed container, heating it to 170°C, evacuating and maintaining the vacuum state; heating the impregnating agent to 170°C, pumping it into the above-mentioned sealed container after the impregnating agent is completely melted, pressurizing it at 1MPa for 3 hours, then cooling it to room temperature, taking it out and carbonizing it at 1200°C for 1 hour;

[0079] The above impregnation-carbonization cycle was repeated three times to obtain a dense carbon-carbon composite material with a density of 1.59 g / cm3 ;

[0080] Finally, methane was used for deposition at 1300 °C for 50 hours to obtain a carbon-carbon composite with a density of 1.74 g / cm 3 , the flexural strength is 179.6MPa.

[0081] Table 1 Process costs of carbon-carbon composite materials of comparative examples 1-2 and embodiments 3-8

[0082]

[0083]

[0084] The average power of the CVD process is 30 kW, the average power of the impregnation-carbonization is 10 kW, and the time for one impregnation-carbonization cycle is 30 hours.

[0085] As can be seen from Table 1, the time taken by the CVD and impregnation-carbonization composite process of the embodiment of the present invention is reduced by more than 70% compared with the simple CVD process, and the energy consumption is only 13-17% of the simple CVD process. Similarly, the labor cost is also greatly reduced, and the cost is greatly reduced.

[0086] Table 1 Properties of carbon-carbon composite materials of Comparative Examples 1-2 and Examples 3-8

[0087]

[0088] It can be seen from Table 2 that, when the impregnating agent modified by carbon nanotubes is used, the flexural strength of the carbon-carbon composite material increases by 30.4-49.1% under similar other conditions, and the effect is obvious.

[0089] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.

[0090] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a high-performance carbon-carbon composite material, characterized in that: The following steps are involved: (1) using a CVD method to control the deposition and shaping of a carbon fiber braid to obtain a preform; (2) using an impregnating agent containing carbon nanotubes to perform an impregnation-carbonization densification cycle on the preform to obtain a dense carbon-carbon composite material; (3) The carbon-carbon composite material is deposited again using the CVD method to obtain a high-performance carbon-carbon composite material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the density of the carbon fiber braid is 0.4-0.7 g / cm 3 The density of the preform is 0.12-0.2g / cm higher than that of the carbon fiber braid. 3 .

3. The preparation method according to claim 2, characterized in that: In the step (1), the CVD method uses methane gas, which is cracked at a high temperature of 900-1300° C. and deposited for 40-60 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step (2), the impregnating agent for the carbon nanotubes is obtained by mixing the carbon nanotubes with asphalt or resin by mechanical stirring.

5. The preparation method according to claim 4, characterized in that: The softening point of the asphalt in the impregnating agent is 90-120° C., the residual carbon rate is 50-61%, and the QI content is less than 2%; or, the resin in the impregnating agent is a thermosetting phenolic resin, and the concentration of the resin solution is 55-70%.

6. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (2), the impregnation-carbonization process comprises: impregnating the preform with an impregnating agent under vacuum, and then carbonizing at 1000-1200° C. for 1-2 hours; The number of impregnation-carbonization cycles is 3-6 times.

7. The preparation method according to claim 6, characterized in that: The density of the dense carbon-carbon composite material is 1.58-1.62 g / cm 3 .

8. The preparation method according to claim 6, characterized in that: If a mixture of carbon nanotubes and asphalt is used as an impregnating agent, the impregnation-carbonization process includes the following steps: placing the preform in a sealed container, heating it to a first target temperature, evacuating and maintaining the vacuum state; heating the impregnating agent to a first target temperature, the first target temperature being 80-100° C. higher than the softening point of the asphalt, pumping the impregnating agent into the sealed container after it is completely melted, pressurizing and maintaining for several hours, then cooling it to room temperature, and taking out the product for carbonization; If a mixture of carbon nanotubes and resin is used as the impregnating agent, the impregnation-carbonization process includes the following steps: heating the sealed container to a second target temperature, evacuating and maintaining the vacuum state; heating the impregnating agent to the second target temperature, and after the temperature stabilizes, pumping the impregnating agent into the sealed container, pressurizing and maintaining it for several hours, and then cooling it to room temperature, taking out the product for drying, curing, and carbonization; wherein the second target temperature is 100-110°C.

9. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (3), the CVD method uses methane gas, which is cracked at a high temperature of 900-1300° C. and deposited for 50-70 hours.

10. The high-performance carbon-carbon composite material obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The density of the high-performance carbon-carbon composite material is 1.72-1.78 g / cm 3 .

Citation Information

Patent Citations

  • Rapid preparation method of low-cost carbon / carbon composite material

    CN105924199A

  • Rapid preparation method of C / C composite material

    CN109384470A

  • Carbon-carbon composite material as well as preparation process and application thereof

    CN111807853A

  • Mould pressing manufacturing method of carbon-carbon crucible support

    CN116375488A

  • Production of carbon / carbon compound material

    JP1989212277A

Cited By

  • Method for preparing carbon / carbon composite material crucible based on continuous fiber winding process

    CN121135456A